Trends in Integrating Green Chemistry and Sustainability into Chemistry Education - Salsabila, Syifa Ayugea; Hernani, Hernani (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
The growing urgency of environmental challenges has emphasized the importance of integrating green chemistry and sustainability concepts into chemistry education. Green chemistry provides a framework for promoting environmentally responsible scientific practices, while sustainability fosters long-term thinking and ethical decision-making among learners. This study aims to analyze recent trends in the integration of green chemistry and sustainability in chemistry learning contexts. A Systematic Literature Review (SLR) was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Twenty peer-reviewed articles published within the last six years and indexed in Scopus and Science and Technology Index (SINTA) were selected from databases including Google Scholar, Education Resources Information Center (ERIC), and Multidisciplinary Digital Publishing Institute (MDPI). The findings indicate that integrating green chemistry and sustainability enhances students' knowledge, interest, and motivation to adopt environmentally responsible attitudes and practices. Despite these benefits, the integration process faces several challenges, such as limited instructional resources, lack of pedagogical strategies, and insufficient contextualization. The study also highlights various effective strategies for implementation, including the use of student worksheets, multimedia tools, and ethnoscience-based approaches that align chemistry learning with local cultural contexts. These insights contribute to the development of more responsive and sustainable chemistry education models, aligning science instruction with global environmental goals and promoting pro-environmental behaviors among future scientists.